Cholesterol Granuloma: Unusual Pitfall for Hodgkin Lymphoma Evaluation With 18F-FDG PET/CT. (October 2021) - Bahri, Haifa; Chassagne-Clement, Catherine; Michallet, Anne-Sophie; Mognetti, Thomas; Nicolas-Virelizier, Emmanuelle
Abstract: Cholesterol granuloma (CG) is a foreign body–type granuloma that forms in response to cholesterol crystals. Its etiology and pathogenesis are unclear. 18 F-FDG is not a tumor-specific agent. Fibroblasts, macrophages, and multinucleated giant cells also take up 18 F-FDG. Like sarcoid granulomas or fibrous dysplasia, CG avidly takes up 18 F-FDG and can mimic tumor involvement. We present 2 cases of histologically proven CG, which has been misinterpreted as active residual Hodgkin lymphoma lesion.